2006
DOI: 10.1111/j.1460-9568.2006.04708.x
|View full text |Cite
|
Sign up to set email alerts
|

IP3 receptor in the hair cells of frog semicircular canal and its possible functional role

Abstract: The presence and functional role of inositol trisphosphate receptors (IP3R) was investigated by electrophysiology and immunohistochemistry in hair cells from the frog semicircular canal. Intracellular recordings were performed from single fibres of the posterior canal in the isolated, intact frog labyrinth, at rest and during rotation, in the presence of IP3 receptor inhibitors and drugs known to produce Ca2+ release from the internal stores or to increase IP3 production. Hair cell immunolabelling for IP3 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…While in our model we are unable to directly measure intracellular calcium we believe the primary source of increased intracellular calcium is from the endoplasmic reticulum. Calcium release from the endoplasmic reticulum is known to be mediated by PLC-IP 3 activation, as well as a ryanodine activation (3,23,38,49,56). Because we have previously shown that the target adenylyl cyclase (AC-V) is localized on the renin-containing granules, it suggests the compartment into which ionized free calcium is being released is the cytoplasm surrounding the granules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in our model we are unable to directly measure intracellular calcium we believe the primary source of increased intracellular calcium is from the endoplasmic reticulum. Calcium release from the endoplasmic reticulum is known to be mediated by PLC-IP 3 activation, as well as a ryanodine activation (3,23,38,49,56). Because we have previously shown that the target adenylyl cyclase (AC-V) is localized on the renin-containing granules, it suggests the compartment into which ionized free calcium is being released is the cytoplasm surrounding the granules.…”
Section: Discussionmentioning
confidence: 99%
“…In the parathyroid glands, the CaSR plays an important role in calcium homeostasis, monitoring serum calcium and signaling for suppression of parathyroid hormone (48) secretion in response to elevated serum calcium. Activation of this Gq protein-coupled receptor by extracellular calcium results in inducing PLC, leading to the generation of IP 3 which binds to an inositol-P 3 receptor on the membrane of the endoplasmic reticulum, opening a calcium channel and releasing calcium from intracellular stores in this organelle (3,23,38,49,56).…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, tricaine methane sulfonate was added to the Ringer solution (final concentration 10 Ϫ4 M, buffered to 7.2 pH). For further details of experimental and recording procedures, see previous papers (7,(15)(16)(17)(18). The afferent discharge recorded from single fibers of the posterior nerve was examined both in terms of spike frequency and of frequency and waveform of miniature excitatory postsynaptic potentials (mEPSPs; see…”
Section: Methodsmentioning
confidence: 99%
“…To analyze quantal transmitter release at the cytoneural junction, we developed in the past an original procedure, capable to measure mEPSP rates of occurrence above 100/s (15,16). The procedure, which was previously used to analyze cytoneural transmission in various experimental conditions (7,17,18), was based on the following steps: 1) identification of the general waveform of the mEPSP by means of fits to the spectral composition and autocorrelation of synaptic recordings: 2nd-to 5th-order autoregressive fits of the autocorrelation are used to estimate the ␥-distribution function best-fitting the "average" event waveform:…”
Section: Quantal Analysis)mentioning
confidence: 99%
“…Neurons adjust calcium signals by regulating the entry of calcium into the cell through the plasma membrane and controlling its release from the intracellular Sarco/endoplasmic reticulum [7]. Calcium influx is regulated by voltage-dependent, ligand-gated Ca 2+ channels, inositol triphosphate (IP 3 ) receptor and ryanodine (Rye) receptor [9,10]. Calcium efflux is regulated by plasma membrane Ca 2+ -ATPase (PMCA), Na/Ca exchanger (NCX) and Sarco/Endoplasmic reticulum Ca 2+ -ATPase (SERCA) [11,12,13].…”
Section: Introductionmentioning
confidence: 99%